2005
DOI: 10.1139/g04-089
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic relationships amongArachissect.Arachisspecies as revealed by AFLP markers

Abstract: Cultivated peanut, Arachis hypogaea L., is a tetraploid (2n = 4x = 40) species thought to be of allopolyploid origin. Its closest relatives are the diploid (2n = 2x = 20) annual and perennial species included with it in Arachis sect. Arachis. Species in section Arachis represent an important source of novel alleles for improvement of cultivated peanut. A better understanding of the level of speciation and taxonomic relationships between taxa within section Arachis is a prerequisite to the effective use of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 36 publications
8
85
1
3
Order By: Relevance
“…The 0.1% difference can be accounted for by subtle differences in the intron repeat sequence between the various samples. Different molecular markers were used by Raina et al (2001) and Milla et al (2005), confirming the conclusions that the genetic base of cultivated peanuts is narrow and that polymorphisms occur only at low levels. Different peanut VTE3 cultivars have been demonstrated to be highly homologous, with the 2 subspecies A. hypogaea ssp fastigiata and A. hypogaea ssp hypogaea being the most likely to share the same diploid wild ancestral species, although validation through further study, including larger cohorts and examination of additional molecular markers is needed to validate these results.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The 0.1% difference can be accounted for by subtle differences in the intron repeat sequence between the various samples. Different molecular markers were used by Raina et al (2001) and Milla et al (2005), confirming the conclusions that the genetic base of cultivated peanuts is narrow and that polymorphisms occur only at low levels. Different peanut VTE3 cultivars have been demonstrated to be highly homologous, with the 2 subspecies A. hypogaea ssp fastigiata and A. hypogaea ssp hypogaea being the most likely to share the same diploid wild ancestral species, although validation through further study, including larger cohorts and examination of additional molecular markers is needed to validate these results.…”
Section: Discussionsupporting
confidence: 62%
“…Studies using amplified fragment length polymorphism (Milla et al, 2005) and fluorescence in situ hybridization (Seijo et al, 2004) methods confirmed that A. hypogaea variant cultivars share the same ancestral origin, and the present study concluded that A. duranensis and A. ipaënsis are likely to be the ancestors of contemporary cultivated species. Singh (1988) synthesized amphidiploid peanuts, hybridized them with different cultivars, and studied the cell morphology and chromosome synapsis.…”
Section: Studies On Vte3 Of Peanutsupporting
confidence: 71%
“…Several authors have shown A. magna to be very similar to A. ipaënsis (Krapovickas and Gregory, 1994;Milla et al, 2005;Moretzsohn et al, 2009), which is the donor of the B genome to the cultivated peanut (Kochert et al, 1996). A. batizocoi was for many years considered a B genome, but was recently re-classified as a K genome species (Robledo and Seijo, 2010).…”
Section: Hybridization and Hybrid Identificationmentioning
confidence: 99%
“…Based on rDNA loci and chromosomes with centromeric heterochromatin, Robledo et al (2009) described three karyotypic subgroups within the A genome and grouped the cultivated peanut with A. duranensis, A. villosa, A. schininii, and A. correntina. Other studies support placing A. hypogaea closely with A. duranensis (Moretzsohn et al, 2004;Milla et al, 2005a;Bravo et al, 2006;Koppolu et al, 2010;Calbrix et al, 2012). The chromosomes of B genome species are karyologically more diverse than those with an A genome (Fernandez and Krapovickas, 1994;Seijo et al, 2004).…”
Section: Cytology and Evolution Of Arachismentioning
confidence: 89%